Single-mode propagation with 205μm mode-field diameter in a passive large pitch fiber - Steinkopff, Albrecht; Jauregui, Cesar; Stutzki, Fabian; Nold, Johannes; Hupel, Christian; Haarlammert, Nicoletta; Bierlich, Jorg; Tuennermann, Andreas; Limpert, Jens (Proceedings of SPIE - The International Society for Optical Engineering, 2019)
We present theoretical and experimental investigations on effective single-transverse mode propagation in very large mode area (VLMA) fibers. Upscaling the mode area of fibers is the most effective approach to reduce the nonlinear interaction and, therefore, to allow for the confinement of high-power radiation without detrimental nonlinear effects. Even though the investigations are carried out in a passive large pitch fiber (LPF), they reveal an intrinsic scaling potential of this design which, if unlocked, will be beneficial for active VLMA fibers in the future. A commercial mode solver based on a full-vectorial finite-difference approach has been used to simulate the confinement losses of the fundamental and higher-order transverse modes. These simulations have revealed that the differential loss in one-missing-hole photonic crystal fibers can be tailored to be larger than 10 dB/m for fiber core sizes larger than 200 μm at 1 μm wavelength. In order to test the theoretical predictions experimental investigations have been performed. Therefore, a rod-type fiber has been fabricated and effective single-mode operation with unprecedented large mode-field diameters has been demonstrated. We were able to achieve single-mode propagation in a passive 1.3 m long LPF with a pitch of 140 μm possessing a mode-field diameter of 205 μm. Even a strong misalignment of the coupling condition did not lead to any significant appearance of higher order modes at the fiber exit, which proves the robustness of the singlemode operation. To the best of our knowledge these results represent the largest dimension of a fundamental transverse mode reported in a waveguide structure at 1 μm wavelength to date. Compared to previous results the mode area is scaled by a factor of about 4 (with respect to active fibers) and a factor of ∼8 (with respect to passive fibers).
CRIS-Team Scopus Importer:2023-04-20
Keywords: Fiber design; Fiber manufacturing; Large mode area fibers